(untitled) (The Planet, 2023)
Post-COVID-19 syndrome is characterized by a number of new, recurring, or persistent symptoms that individuals suffer for more than four weeks after contracting COVID-19. In some individuals, the post-COVID-19 condition might linger for months or years or result in impairment. On December 31, 2019, Hubei province, Wuhan, China, reported the discovery of an outbreak of the novel coronavirus nCoV-19 (SARS-CoV-2), which is the cause of the coronavirus disease-19 (COVID-19). Up till May 7th, 2021, there were 3,278,510 fatalities and about 157,343,044 confirmed cases worldwide [1]. On March 11, 2020, the World Health Organization (WHO) proclaimed COVID-19 a pandemic. The second wave of the Coronavirus Disease 2019 (COVID-19) pandemic, which was the greatest problematic threat to public health, affected the entire planet. It posed a serious problem for the fields of science, medicine, and public health [2]. The World Health Organization estimated that 80% of infections were minor or asymptomatic, 15% had moderate to severe symptoms (requiring oxygen), and 5% had critical infections that needed ICU care.In Bangladesh, COVID-19 cases were confirmed 2,031,797 cases between 3 January 2020 and 14 October 2022, and 29,393 deaths were reported to the WHO [3]. Numerous clinical investigations have shown that a significant fraction of COVID-19 hospital patients still experience one or more health issues months after leaving the hospital [4,5]. The name "Post COVID-19 condition" has just been recommended by a working group under the WHO as a preliminary clinical case definition. This criterion is predicated on the presence of a structured consensus process three months from the onset of symptoms or the date of the SARSCoV2 infection, which lasts for at least two months [6,7]. Numerous studies have shown that between 50 and 87% of hospitalized patients around the world experienced at least one post-COVID-19 symptom for a few weeks after convalescence or hospital discharge, and that 20% of COVID-19 patients continued to experience symptoms for longer than three months despite a lessened severity[8]. Following COVID-19, such enduring and incapacitating symptoms suggest that the outbreak’s negative effects did not end with recovery from the acute phase of the illness and that the pandemic is likely to continue to have an effect on people, families, and social groupings [9]. Less than 20% of COVID-19 patients require hospital admission, but more than 80% of them require therapy ranging from oxygen to ventilator support [10,11]. Those over the age of 65 and those with co-morbidities such as diabetes, HTN, COPD, heart disease, renal illness, etc. are at greater risk of developing long-term COVID-19 symptoms.Several studies over the world have suggested that around 10-15% patientsdevelopweakness, tiredness, breathless, cough, memory loss, anorexia, constipation, excessive sweating, swelling of legs, alopecia, chest pain and allergy etc. Though COVID-19 is an acute viral illness in which most patients make a full recovery in a matter of weeks, but even after a full recovery, a significant number of patient experience persistent, recurring or newsymptoms for more than four weeks, even for months or years after contracting COVID-19 and may result in impairment in different fields.